2008
DOI: 10.1136/emj.2006.044776
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of pain during intravenous catheter placement using a topical skin coolant in the emergency department

Abstract: Our study failed to detect a difference in pain perception resulting from the pre-procedural application of a skin coolant associated with i.v. placement in the ED setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…There have been several efforts to reduce needleinduced pain or distress 4,5 . However, even if a uniform nociceptive stimulus is applied, individuals may complain of pain to varying degrees because pain is a subjective experience to a noxious stimulus and many individual factors contribute to pain perception.…”
mentioning
confidence: 99%
“…There have been several efforts to reduce needleinduced pain or distress 4,5 . However, even if a uniform nociceptive stimulus is applied, individuals may complain of pain to varying degrees because pain is a subjective experience to a noxious stimulus and many individual factors contribute to pain perception.…”
mentioning
confidence: 99%
“…For permission to post online, reprint, adapt, or reuse, please email pubpermissions@ons.org effects of intradermal injection of normal saline with benzyl alcohol or lidocaine in 40, 47, and 221 preoperative adults, respectively. Other researchers investigated alternative methods of analgesia for IV insertions, including topical skin coolants (Hartstein & Barry, 2008), a topical local anesthetic cream (Luhmann, Hurt, Shootman, & Kennedy, 2004) or patch (Sethna et al, 2005), and selfselected music therapy (Jacobsen, 1999), all with positive results. Svensson, Rosen, and Nilsson (2006) randomized 125 ambulatory patients to receive either local warming for one minute or no treatment prior to IV insertion and found that local warming did not have any pain-reducing effect.…”
mentioning
confidence: 99%
“…Although proven effective for intramuscular injections (8), literature has been conflicting on whether vapocoolant sprays are also effective for IV catheter placement. (9–16)…”
Section: Introductionmentioning
confidence: 99%